Emancipatory discourses: Utilizing Kleinian psychoanalysis and poststructuralist theory to deconstruct and (re)present phallocentric themes in "Rebecca" and "American Beauty" - Hosking, Lynda (University of Ottawa (Canada), 2007)
This thesis develops a theoretical methodology that deconstructs and (re)presents phallocentric themes in cultural narratives. This methodology, I argue, is an analytical strategy that displaces the primacy of the mythic structures of the Oedipal narrative in contemporary Western culture because it attends to other means of subjectivization and highlights sites of resignification. The theorization accomplishes three related tasks: it identifies areas in discourse that promote images of integration and wholeness; it reveals the performative nature and historical contingency of phallocentric discourses in cultural media; and it allows for the emergence of de-centered subjects. Drawing from Melanie Klein and Judith Butler, I argue that the Oedipal drama is not the means by which bodies in nature become subjects in culture; rather, it is a discourse that sustains the power and privilege of shifting conceptions of masculinity through its perpetual iteration. The symbolic order is the temporal regulation of signification that describes the atmosphere in which consent and regulation are secured, but it does not determine it. If the Oedipal complex is understood to be a performative expression of dominant discourse rather than a natural process, the Oedipal complex can be said to produce that which it claims only to describe. A poststructuralist psychoanalytic criticism interrogates the text, searching for traces of the always already said embedded in discourse. The analyses of the films Rebecca and American Beauty demonstrate that a Kleinian-poststructuralist methodology identifies new and different interpretations of texts.
Keywords: Religion, General.; Cinema.